The mantle structure below petit-spot volcanoes - Naoto Hirano; Shiki Machida (Communications Earth & Environment, 2022)
The compositional fingerprint of petit-spot magmas represents an enriched mantle source and carbonatitic or carbonated silicate melts below the oceanic lithosphere, suggests a synthesis of geochemical analyses on petit-spot volcanism.